Studi Pembuatan Nori Artifisial Daun Kelor dengan Variasi Penambahan Bahan Pengikat - Widyastuti, Reza; Novita, Dewi; Nugroho, Muhamad Bayu; Muflihati, Iffah (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
Nori is a traditional Japanese food made from thin sheets of Phorphyra sea algae. This study aims to determine the effect of binder in the form of agar, CMC and tapioca to the characteristics of artificial nori Moringa leaves. This study used a completely randomized design (CRD) with 3 variations of the binder used: tapioca flour, agar, and CMC with a concentration of 5%. The results of the analysis of the highest water content and ash content were the samples using CMC binder of 10.7067% and 17.2233%. The highest color analysis results on the use of CMC binder obtained the L value of 21.30, the value of a * = -4.26 and the value of b * = 57.33. The most preferred nori by panelists is nori with the addition of CMC.